Characteristics and outcomes of patients on concurrent direct oral anticoagulants and targeted anticancer therapies—TacDOAC registry: Communication from the ISTH SSC Subcommittee on Hemostasis and Malignancy. (29th July 2021) - Wang, Tzu‐Fei; Baumann Kreuziger, Lisa; Leader, Avi; Spectre, Galia; Lim, Ming Y.; Gahagan, Andrew; Gangaraju, Radhika; Sanfilippo, Kristen M.; Mallick, Ranjeeta; Zwicker, Jeffrey I.; Carrier, Marc
Abstract: Background: Cancer patients are increasingly prescribed direct oral anticoagulants (DOACs) and targeted anticancer therapies, but limited data are available on the outcomes during concurrent use. Objectives: We conducted an international registry through the Scientific and Standardization Committee of the ISTH to evaluate the characteristics, bleeding, and thrombotic outcomes in patients receiving concurrent DOACs and targeted anticancer therapies. Patients/Methods: Patients receiving concurrent DOACs for venous thromboembolism (VTE) or atrial fibrillation and selected targeted anticancer therapies were followed for 6 months after the start of concurrent use. Data including patient and cancer characteristics, major bleeding, non‐major bleeding events, and venous or arterial thromboses were collected. Results: Two hundred and two patients were included from six institutions in the United States and Israel. The most common malignancies were hematologic ( N = 57, 28.2%), followed by breast ( N = 50, 24.8%) and lung ( N = 44, 21.8%). The most common anticancer therapies were epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) inhibitors ( N = 43, 21.3%), followed by Bruton's tyrosine kinase (BTK) inhibitors ( N = 42, 20.8%) and palbociclib ( N = 42, 20.8%). During follow‐up, there were 9 major bleeding and 12 non‐major bleeding events, corresponding to cumulative incidences of 4% (95% confidence interval [CI]: 2–8%) and 6% (95% CI: 3–10%), respectively. The cumulative incidence of major bleeding events was highest in BTK inhibitor users (10%). There were 3 VTE and 2 arterial thromboses, corresponding to cumulative incidences of 1.5% (95% CI: 0.4–4.0%) and 1.0% (95% CI: 0.2–3.3%), respectively. Conclusions: In this cohort receiving concurrent DOACs and targeted anticancer therapies, the incidence of bleeding is higher compared to thrombosis, particularly with BTK inhibitors. Future larger prospective studies are needed.